Food Noise Among Healthcare Students and Healthcare Professionals in Al-Ahsa, Saudi Arabia: A Cross-Sectional Study - Saba Alarfaj; Manal Alqahtani; Abdullah Almaqhawi (Nutrients, 2026)
Background: Food noise describes persistent, intrusive thoughts about food, eating, and cravings that occur in the absence of physiological hunger. Its occurrence among healthcare students and professionals in Saudi Arabia is unknown. This study measured food noise in this group in Al-Ahsa, described the proportion meeting study-defined severity thresholds, and identified its main correlates. Methods: In this cross-sectional study, healthcare students and professionals in Al-Ahsa completed a bilingual (Arabic–English) electronic questionnaire capturing demographic and lifestyle characteristics, a 14-item food noise scale adapted from the Food Thought Suppression Inventory (each item rated 1–5; total range 14–70), the SCOFF eating disorder screen, and the four-item Perceived Stress Scale. The factor structure of the food noise scale was examined by exploratory factor analysis with parallel analysis and random split-half replication. Severity was graded from the mean item score as low, moderate, or high using exploratory thresholds, and associations were tested using t-tests, one-way analysis of variance, the Pearson correlation, and complete-case multivariable linear regression with robust standard errors and six sensitivity analyses. Results: Among 593 participants (mean age 25.7 years; 67.5% women; 60.0% students), the food noise scale was unidimensional (Kaiser–Meyer–Olkin 0.95; one eigenvalue above both unity and the parallel analysis threshold; 41.8% of variance explained; loadings 0.50 to 0.74) and internally consistent (Cronbach alpha 0.91). The mean total score was 41.9 (standard deviation 12.7). At least moderate food noise was present in 75.9% of participants (95% CI 72.3 to 79.2) and high food noise in 29.0% (95% CI 25.5 to 32.8). A positive SCOFF screen was recorded in 70.2% (95% CI 66.3 to 73.7), and the mean perceived stress score was 8.1 (standard deviation 2.8). In the adjusted model (n = 573; unadjusted R-squared 0.279, adjusted R-squared 0.266), food noise was independently associated with the SCOFF score (B 3.85 per point) and perceived stress (B 0.69 per point), both of which held across every sensitivity analysis, although both relationships proved concave rather than linear. Weaker associations with age (B 0.19 per year) and any night shift work (B 2.45) did not survive alternative model specifications, and crude differences by sex, role, weekly hours, and fasting did not persist after adjustment. Conclusions: Food noise was common in this sample and tracked eating disorder risk and perceived stress more closely than demographic or occupational characteristics. Because recruitment was by convenience and the severity thresholds are exploratory rather than validated, the proportions reported here describe this sample and should not be read as population prevalence. The findings provide a first benchmark for the construct in this population and support attention to the cognitive dimension of eating within health professions settings.